Environmental Learning Using Interactive Media to Increase Coastal Local Knowledge About Environmental Problems Mitigation in Luwu Raya Sulawesi - Asri Asri; Rusdiana Junaid (Universitas Cokroaminoto Palopo, 2021)
This research aims to mitigate environmental problems through learning by using documentary films for fishermen groups whose environmental conditions have been damaged for years. The fishermen group were from Belopa, Harapan, and Munte Village, North Luwu Regency. The method used was action research by creating learning tools validated by two education experts in two learning actions to observe the learning components' feasibility. The validation of the learning plan and documentary film was in the